2001
DOI: 10.1186/1471-2350-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Mn-SOD and EC-SOD Genes and Their Relationship to Diabetic Neuropathy in Type 1 Diabetes Mellitus

Abstract: BackgroundOxidative stress, resulting in a marked increase in the level of oxygen free radicals (OFR), has been implicated in the etiology of diabetic neuropathy (DN). Antioxidant enzymes may protect against the rapid onset and progression of DN, by reducing the excess of OFR and peroxide. Mutations and polymorphisms in the genes encoding such enzymes may therefore result in predisposition to DN. We investigated the role of genes encoding two antioxidant enzymes, mitochondrial (Mn-SOD) and extracellular (EC-SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 30 publications
6
29
0
1
Order By: Relevance
“…Because of the above-mentioned inconsistent results from relatively small studies underpowered to detect the effect, a meta-analysis is the appropriate approach to obtain a more definitive conclusion regarding the role of SOD2 gene C47T polymorphism on risk of diabetes mellitus and DMI including diabetic nephropathy, diabetic retinopathy and DPN. Our meta-analysis, of 17 published articles [6,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] with 31 outcomes from different ethnic origins, allowed a much greater possibility of reaching reasonably strong conclusions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of the above-mentioned inconsistent results from relatively small studies underpowered to detect the effect, a meta-analysis is the appropriate approach to obtain a more definitive conclusion regarding the role of SOD2 gene C47T polymorphism on risk of diabetes mellitus and DMI including diabetic nephropathy, diabetic retinopathy and DPN. Our meta-analysis, of 17 published articles [6,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] with 31 outcomes from different ethnic origins, allowed a much greater possibility of reaching reasonably strong conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…Chistyakov et al [6] first showed the significant protective effect of C47T polymorphism in SOD2 gene on DPN risk in 82 DPN cases and 84 non-DPN controls in type 1 diabetes mellitus patients, but no association with risk of type 1 diabetes mellitus was found in 166 type 1 diabetes mellitus cases and 88 normal controls in a Russian population. Nevertheless, results of subsequent studies about the effect of this polymorphism on risk of diabetes mellitus, including type 1 and type 2 diabetes, and of DMI including diabetic nephropathy, diabetic retinopathy and DPN were conflicting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency distributions of C and T alleles were found to be respec- has the similar CC genotype frequency as seen in AfricanAmerican [35], Finn [36], and Italian populations [37]. We detected considerably lower CC genotype frequency than those found in Korean [38], Japan [39], Chinese [40] and Taiwan [41] populations and higher frequencies than those found in American [23], Polish [42], Danish [43], German [44] and Russian [45] populations. Eventually, CC genotype frequency in populations of the eastern countries, were lower (between 0-17%) found than the western countries (between 42-67%) ( Table 4).…”
Section: Resultsmentioning
confidence: 52%